Factors associated with glycemic control in type 2 diabetes patients at primary care unit, Pathumrat district, Roi-Et province, Thailand - Niyom Pragosuntung (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2010